1999
DOI: 10.2337/diabetes.48.6.1270
|View full text |Cite
|
Sign up to set email alerts
|

Free fatty acid-induced insulin resistance is associated with activation of protein kinase C theta and alterations in the insulin signaling cascade.

Abstract: To examine the mechanism by which free fatty acids (FFAs) induce insulin resistance in vivo, awake chronically catheterized rats underwent a hyperinsulinemic-euglycemic clamp with or without a 5-h preinfusion of lipid/heparin to raise plasma FFA concentrations. Increased plasma FFAs resulted in insulin resistance as reflected by a approximately 35% reduction in the glucose infusion rate (P < 0.05 vs. control). The insulin resistance was associated with a 40-50% reduction in 13C nuclear magnetic resonance (NMR)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

51
716
0
14

Year Published

2003
2003
2008
2008

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 1,100 publications
(781 citation statements)
references
References 8 publications
51
716
0
14
Order By: Relevance
“…The rise in plasma levels of NEFAs has been shown to induce insulin resistance [5][6][7][8]. In line with these studies, it has been demonstrated that CD36 knockout mice have improved insulin sensitivity in muscle, implying that fatty acid flux into the cells plays a critical role in insulin resistance [9].…”
Section: Introductionmentioning
confidence: 81%
“…The rise in plasma levels of NEFAs has been shown to induce insulin resistance [5][6][7][8]. In line with these studies, it has been demonstrated that CD36 knockout mice have improved insulin sensitivity in muscle, implying that fatty acid flux into the cells plays a critical role in insulin resistance [9].…”
Section: Introductionmentioning
confidence: 81%
“…The antioxidant property of vitamin E is often considered a key activity, although vitamin E does cause other effects that could potentially modify the action of insulin. For example, vitamin E inhibits protein kinase C activity, which has been associated with insulin resistance experimentally [19]. Vitamin E regulates several genes; for example, it upregulates the expression of PPARG, the gene for peroxisome proliferator activated receptor γ (PPARγ) [20].…”
Section: Discussionmentioning
confidence: 99%
“…Mounting evidence indicates that activation of c-Jun N-terminal kinase (JNK), IKK and conventional PKC is central to the development of insulin resistance in response to obesity -mediated by the aforementioned fatty acidinduced ER stress, ROS production, TLR activation and inflammatory signalling by TNF . JNK, IKK and PKC have all been reported to inhibit insulin action by phosphorylating IRS1 on serine [80][81][82] . Serine phosphorylation of IRS1 disrupts insulin-receptor signalling through several distinct mechanisms and blocks insulin action 83,84 .…”
Section: Nature Reviews | Molecular Cell Biologymentioning
confidence: 99%